Lactic Acid Fermentation by L. leichmannii Exposed to Some Alkaloids - Singh, S.P.; Sandani, G.; Dubey, J.K.; Kumar, A.; Kumar, Bijay; Shamim, Md. (Asian Journal of Chemistry, 2010)
The influence of different alkaloids on lactic acid fermentation by L. leichmannii was studied. It was found that berberine sulphate, strychnine nitrate and papaverine hydrochloride have been slightly stimulant at all the concentrations used whiie ricinine was found to be stimulant at lower concentrations only.